THE INFLUENCE OF INTELLECTUAL CAPITAL ON FINANCIAL PERFORMANCE PROPERTY AND REAL ESTATE COMPANY - Naim Kharima Saraswati; Sri Hartoko (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Companies with good IC can manage their assets effectively and efficiently, boosting financial success. IC's value creation impacts the company's financial success, so it must be prioritized. This study examines intellectual capital's impact on financial performance. The companies used as research objects are property and real estate sector companies listed on the Indonesia Stock Exchange from 2015-2019. This study took a sample with a purposive sampling method and found 34 companies with a total of 170 observations for 5 years. The method used in this study is a multiple linear analysis by analyzing VAHU, STVA, and VACA as independent variables and measured by financial performance using Return on Assets (ROA) as the dependent variable. The results of this study are the influence of VACA, VAHU, and STVA on financial performance.